Critical Success Factors of Public Private Partnership (PPP) Implementation in Malaysia - Ismail, Suhaiza (2013)
Purpose: This paper aims to examine the importance of the success factors as perceived by the overall respondents. Also, the study intends to identify the differences concerning the importance of the success factors between the public and private sectors. Methodology: A questionnaire survey was used to elicit the perceptions of public and private sectors on the key success factors of PPP project in Malaysia. In total, 179 usable responses were obtained and analysed using SPSS to rank the importance of the success factors and to examine the differences in the perceptions between the government and the private sector. Findings: The overall results show that ‘good governance’, ‘commitment of the public and private sectors’, ‘favourable legal framework’, ‘sound economic policy’ and ‘availability of finance market’ are the top five success factors of PPP implementation in Malaysia. Although the rankings of many factors were different between the public and private sectors, there were no significant differences in the perception of the public and private sectors concerning the importance of the success factors except for a few factors. Originality/value: This paper highlights not only the important success factors for PPP implementation in Malaysia, but also offers evidence concerning the importance of the factors of the two key parties involved in PPP– the public sector and private sector. Keywords: Public Private Partnerships, critical success factors, Malaysia, government